2022
DOI: 10.1007/s00216-022-03947-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacteria by poly-aromatic hydrocarbon biosensors

Abstract: Availability of data and material Not applicable Code availability Not applicable Authors' contributionsYS and IS conceived the idea. YS, SH, VB and IS designed the experiments. YS and YF performed the main experiments. YS wrote the paper. IS provided all funding for the project. IS supervised the entire research project.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…2a). The spectral fingerprints of the amino acids Tyrosine and Tryptophan (Tyr + Trp) (λ Ex max= 280 nm, λ Em max = 350 nm)(Shlosberg et al, 2021a), NADPH (λ Ex max= 280 nm, λ Em max= 350 nm)(Shlosberg et al, 2020), and chlorophyll a (λ Ex max= 480nm, λ Em max = 690 nm)(Shlosberg et al, 2020) were identified. Intact spinach cuttings and cuttings grasped by the non-sharp edge of the anode clips (as in the BPEC setup, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2a). The spectral fingerprints of the amino acids Tyrosine and Tryptophan (Tyr + Trp) (λ Ex max= 280 nm, λ Em max = 350 nm)(Shlosberg et al, 2021a), NADPH (λ Ex max= 280 nm, λ Em max= 350 nm)(Shlosberg et al, 2020), and chlorophyll a (λ Ex max= 480nm, λ Em max = 690 nm)(Shlosberg et al, 2020) were identified. Intact spinach cuttings and cuttings grasped by the non-sharp edge of the anode clips (as in the BPEC setup, Fig.…”
Section: Methodsmentioning
confidence: 99%